INEDUC : pratiques numériques des adolescents et territoires - Mickaël Le Mentec; Pascal Plantard (Netcom)
The INEDUC project focuses on educational inequalities. It plans to analyze the educational pathways of teenagers aged 13 to 15 years, linking their schooling, their leisure activities during free time and their digital practices. The results show that the territorial variable does not appear as discriminating on digital equipment but it is, as well as social variable, since we are interested in digital uses and coaching practices at home. For the sake of social and spatial justice, the article shows how some colleges are trying to compensate for inequalities territories and social situations.